Proceedings of the Third International Conference on Economic and Business Management (FEBM 2018) 2018
DOI: 10.2991/febm-18.2018.95
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fuzzy Logic in the Enterprise’s Fundamental Strength Assessment

Abstract: The main aim of the paper is to present a practical application of an original enterprise's fundamental strength assessment fuzzy model, as an alternative to dominant in the literature solutions based on taxonomic methodology. Proposed model is an attempt to combine the fuzzy methodology with financial ratios (both in static and dynamic form) and in contrast to the most popular solutions in this area, it covers wider range of enterprise's performance dimensions, in particular financial condition, financial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The fuzzy model proposed is intended to be used as a tool for managerial decisionmaking at enterprises. Meanwhile, the models proposed by other researchers are based on the listed enterprises and focus more on support to the investment process (Nawrocki, 2018). The fuzzy model proposed here may help the owners and managers of micro and small enterprises detect fraud of business partners and reduce the business risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The fuzzy model proposed is intended to be used as a tool for managerial decisionmaking at enterprises. Meanwhile, the models proposed by other researchers are based on the listed enterprises and focus more on support to the investment process (Nawrocki, 2018). The fuzzy model proposed here may help the owners and managers of micro and small enterprises detect fraud of business partners and reduce the business risk.…”
Section: Discussionmentioning
confidence: 99%
“…The key issue was to identify how the respective researchers use various AI techniques to solve financial problems. Following the systematic literature review, the AI methods used for detection of fraudulent financial statements were identified, such as fuzzy logic (Arora and Saini, 2013;Maltoudoglou et al, 2015;Antonelli et al, 2016;Omar et al, 2017;Nawrocki, 2018;Čičak and Vašiček, 2019;Tiwari et al, 2020), neural networks (Antonelli et al, 2016;Omar et al, 2017;Tiwari et al, 2020), neuro-fuzzy (Arora and Saini, 2013;Antonelli et al, 2016;Rostamy-Malkhalifeh et al, 2021) and decision trees (Arora and Saini, 2013;Chen et al, 2014;Lin et al, 2015;Antonelli et al, 2016;Omar et al, 2017;Zhang, 2020). Hence, previous empirical studies on these AI methods were analysed for finding an appropriate method to us.…”
Section: Innovative Research Methods For Detection Of Fraudulent Fina...mentioning
confidence: 99%
See 3 more Smart Citations